EFFECT OF PERSONAL SELLING AND DISTRIBUTION ON MARKETING PERFORMANCE MODERATED BY REGULATION (CASE STUDY AT PT. KIMIA FARMA TRADING, CAB. MEDAN) - Hazmanan Khair; Satria Tirtayasa; Intan Julita Hartati (Institute of Computer Science (IOCS), 2022)
This study aims to examine and analyze the influence of personal selling and distribution on marketing performance directly or moderated by regulation. The research method used is quantitative which is associative by using primary data, namely interviews, and secondary data, namely sales, distribution, and data sourced from PT. Kimia Farma Trading Medan Branch. The research instrument was carried out using observation, interviews, and documentation. The informants are determined and determined based on the number needed, but based on consideration of the function and role of information according to the focus of the research problem. So that the informants in the study are 58 people who are managers at PT. Kimia Farma Trading Medan Branch. The results of this study indicate that this study shows that the direct effect of personal selling has a positive and significant effect on Marketing Performance (Marketing). Furthermore, the distribution has a positive but not significant effect on Marketing Performance (Marketing). Regulation has a negative and insignificant effect on Marketing Performance (Marketing). With the results of the moderating effect analysis, it can be seen that the regulation mediates the influence of personal selling and distribution on Marketing Performance (Marketing), and regulation mediates the influence of personal selling but not moderating distribution on Marketing Performance (Marketing) PT.Kimia Farma Trading Cab. Field.